Mutagenicity evaluation of Anastatica hierochuntica L. aqueous extract in vitro and in vivo - Md Zin, Siti Rosmani; Mohamed, Zahurin; Alshawsh, Mohammed Abdullah; Wong, Won Fen; Kassim, Normadiah M. (SAGE Publications, 2018)
Anastatica hierochuntica L. (A. hierochuntica), a folk medicinal plant, was evaluated for mutagenic potential via in vitro and in vivo assays. The in vitro assay was conducted according to modified Ames test, while the in vivo study was performed according to Organisation for Economic Co-operation and Development guideline for mammalian erythrocyte micronucleus assay. Four groups (n= 5 males and 5 females per group) Sprague Dawley rats were randomly chosen as the negative control, positive control (received a single intramuscular injection of cyclophosphamide 50 mg/kg), 1000 and, 2000 mg/kg A. hierochuntica aqueous extracts. All groups except the positive control were treated orally for three days. Findings of the in vitro assay showed mutagenic potential of AHAE at 0.04 and 0.2 mg/ml. However, no mutagenic effect was demonstrated in the in vivo study up to 2000 mg/kg. No significant reduction in the polychromatic and normochromatic erythrocytes ratio was noted in any of the groups. Meanwhile, high micronucleated polychromatic erythrocytes frequency was seen in cyclophosphamide-treated group only. These findings could perhaps be due to insufficient dosage of A. hierochuntica aqueous extracts to cause genetic damage on the bone marrow target cells. Further acute and chronic in vivo toxicity studies may be required to draw pertinent conclusion on the safety aspect of A. hierochuntica aqueous extracts consumption. Impact statement: In this paper, we report on the mutagenicity evaluation of Anastatica hierochuntica aqueous extract. This is a significant research in view of the popularity of this herb consumption by the people across the globe despite of limited scientific evidence on its toxicity potential. This study is intended to encourage more extensive related research in order to provide sufficient evidence and guidance for determining its safe dosage.